Performance Characteristics of Silane Silica Modified Asphalt - Xuedong Guo; Mingzhi Sun; Wenting Dai; Shuang Chen (Advances in Materials Science and Engineering)
At present there are many kinds of fillers and modifier used for modified asphalt, but the effect of modifier differs in thousands of ways; most of them can increase the high temperature performance of asphalt, but the modified effect of low-temperature crack resistance, water stability, and antifatigue performance is different. Aiming at the subsistent problems, this paper innovatively puts forward the idea of taking the silane silica (nanosilica modified with silane coupling agent) as filler to develop one kind of modified asphalt concrete which has excellent comprehensive performance based on the idea of enhance the whole performance of asphalt concrete and interface consolidation strength between aggregate and asphalt at the same time. The best mixing amount of silane silica and the production process of modified asphalt were conducted by contrasting the test date as penetration, viscosity, and softening point; the aging of asphalt and modified asphalt was analyzed by TG test, the superiority of silane silica modified asphalt is more clearly understandable by chemical analysis results. Meanwhile it is proved that silane silica has positive effect to improve the mixture of high and low temperature performance, water stability, and aging resistance through a series of road performance tests.